(untitled) (Research, Society and Development, 2020)
This research aimed to determine the effects of mercury use in whitening creams for the general public. This research used descriptive-qualitative approach, the method that used in this research is literature study which implemented by recording the previous findings regarding to the variables of conflict. WHO states that more than 90 creams from 15 countries have detectable mercury concentrations below 1 ppm. Thirty-four creams (10% of the sample) was found that have high mercury levels, that is, above 1 ppm, in four of the 13 samples from Indonesia, overall, mercury concentrations in this particular product ranged from 93 ppm to over 16,000 ppm. Long-term adverse effects of using mercury cream on health.